ASSOCIATIVE MEANING IN KAMIL KAILANI’S ABU AL-HASAN: GEOFFREY LEECH SEMANTIC STUDY - Ihkam, Muhammad Hadiyan; Nafisah, Nadya (Annual International Conferences on Language, Literature, and Media, 2023)
The associative meaning helps readers understand the differences between similar words but with different meanings and nuances in the context of a story. By understanding the associative meaning of each word or phrase used in a short story, readers can better understand the story's characterization, setting, and theme. For example, words used to describe the characters or setting of a story can have the same meaning or be associatively related, which can give the story different connotations. This study aims to analyze the associative meaning in the short story Abu Al-Ḥasan by Kamil Kailani based on the perspective of Geoffrey Leech. The type of research used is descriptive qualitative. The data source for this research is the short story Abu Al-Ḥasan by Kamil Kailani. The data collection method used is the technique of observing and noting. Researchers perform data reduction, data presentation, and concluding data analysis techniques. The result of this study is that associative meaning is a word or phrase that relates to a situation outside the language itself. Associative meaning includes five types of meaning, namely reflective meaning, collocative meaning, affective meaning, stylistic meaning, and connotative meaning. The associative meaning in the short story Abu Al-Ḥasan by Kamil Kailani includes four stylistic meanings, two collocative meanings, two affective meanings, and two connotative meanings.